Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s11136-019-02345-z
|View full text |Cite
|
Sign up to set email alerts
|

The construct validity and responsiveness of the EQ-5D-5L, AQL-5D and a bespoke TTO in acute asthmatics

Abstract: Purpose Measuring quality of life in acute asthmatics is challenging, especially when asthma attacks can occur sporadically. Several questionnaires can be used to measure quality of life in this patient group; however, psychometric testing is limited on questionnaires that can be used to estimate Quality Adjusted Life years. The objective of this study is to assess the construct validity (convergent and discriminative validity) and responsiveness of the EuroQol-5-Dimensions 5-Level (EQ-5D-5L), Asthma Quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Responsiveness of the EQ-5D-5L in patients with improved health states was also studied in other populations; however, the results were inconsistent. In patients with acute asthma who underwent one month of treatment and self-reported improved health states, the index value had moderate to large responsiveness with the effect size ranged from 0.63 to 0.95 [50]. Golicki et al revealed that the EQ-5D-5L was consistently responsive in patients who had a stroke, who displayed improved health four months after treatment: the index value showed a moderate ES (0.51-0.71) and a moderate to large SRM (0.69-0.86), while the ES of EQ VAS ranged from 0.51 to 0.65 and the SRM ranged from 0.59 to 0.69 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Responsiveness of the EQ-5D-5L in patients with improved health states was also studied in other populations; however, the results were inconsistent. In patients with acute asthma who underwent one month of treatment and self-reported improved health states, the index value had moderate to large responsiveness with the effect size ranged from 0.63 to 0.95 [50]. Golicki et al revealed that the EQ-5D-5L was consistently responsive in patients who had a stroke, who displayed improved health four months after treatment: the index value showed a moderate ES (0.51-0.71) and a moderate to large SRM (0.69-0.86), while the ES of EQ VAS ranged from 0.51 to 0.65 and the SRM ranged from 0.59 to 0.69 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Responsiveness of the EQ-5D-5L in patients with improved health states was also studied in other populations, but results were inconsistent. In acute asthmatics patients who underwent 1 month of treatment and self-reported improvement in health states, the UI had moderate to large responsiveness with effct size of 0.63 to 0.95 [40]. Golicki et al revealed that the EQ-5D-5L was consistently responsive in stroke patients with improved health 4 months after treatment, which UI showing moderate ES (0.51-0.71) and moderate to large SRM (0.69-0.86), and EQ VAS range from 0.51 to 0.65 for ES and 0.59 to 0.69 for SRM [41].…”
Section: Discussionmentioning
confidence: 99%
“…Responsiveness of the EQ-5D-5L in patients with improved health states was also studied in other populations; however, the results were inconsistent. In patients with acute asthma, who underwent one month of treatment and self-reported improved health states, the index value had moderate to large responsiveness with the effect size ranged 0.63 to 0.95 [50]. Golicki and colleagues revealed that the EQ-5D-5L was consistently responsive in patients who had a stroke, who displayed improved health four months after treatment: the index value showed a moderate ES (0.51-0.71) and a moderate to large SRM (0.69-0.86), while the ES of EQ VAS ranged from 0.51 to 0.65 and the SRM ranged from 0.59 to 0.69 [51].…”
Section: Discussionmentioning
confidence: 99%